Cross‐organisational data sharing framework based on blockchain‐probes. Issue 2 (19th July 2022) - Jia, Xiaofeng; Xu, Wenjing; Deng, Pan; Gao, Song; Tang, Lin; Wang, Yuhang; Zhang, Min; Bao, Lulu; Lin, Dingding
Abstract: With the development of information technology, various social fields have gradually realised informatisation and digitisation, and today's society has entered the era of big data. A large amount of data exists in different departments and systems. At present, cross‐organisational data sharing is often realised by point‐to‐point authorisation. However, there are still some threats in the management and control schedule for the whole region. To realise secure and credible data sharing, this paper proposes a cross‐organisational data‐sharing framework based on Blockchain‐Probes using distributed digital identity technology. By using a star data link of the complex network, our system realises the synchronisation of heterogeneous data sources by using a data probe as the inter‐central transmission carrier to link different data sources. The proposed framework is applied to the real scenario; compared with the traditional method, the efficiency and accuracy are improved, and the total cost is reduced by 60%. The framework could be employed in multiple complex system application scenarios such as transportation, finance and urban management.